Vpliv nekaterih ključnih dejavnikov okolja na življenjsko dobo optičnih nosilcev podatkov - Kunej, Drago (Knjižnica, 2011)
In recent years, the concept of content preservation rather than carrier preservation has become the norm with regard to long-term digital preservation. Nonetheless, the life expectancy of digital carriers is important because, in addition to other digital system parameters, it determines the migration time of digital content. In general, a cleaner, cooler, drier, and more stable environment extends the life expectancy, and appropriate protection of individual types of carriers is based on understanding the vulnerability of the carrier and consequently on providing optimal storage conditions and appropriate handling. This paper presents the effects of specific environmental factors (i.e., temperature, humidity, and light) on the life expectancy of physical digital recording media, with an emphasis on optical media. Although optical discs are just one of the various methods of digital data storage today, they continue to be a popular archive medium. It should be noted that optical discs are not permanent recording media, as is often wrongly believed, and that their life expectancy is significantly influenced by environmental factors. At the ZRC SAZU Institute of Ethnomusicology, an experiment was conducted to analyze the durability of digital records saved on CD-Rs that were exposed to light in everyday working conditions. The results showed that exposing recordable optical discs to light, especially direct sunlight, can result in complete destruction of the data recorded within a few days or weeks. This confirmed the importance of careful handling, appropriate storage, and regular testing of digital carriers.
Keywords: arhivi; dokumentacija; digitalne zbirke; digitalni viri; trajno ohranjanje